Hydrodynamic Studies on a Trickle Bed Reactor for Foaming Liquids - Renu Gupta; Ajay Bansal (Bulletin of Chemical Reaction Engineering & Catalysis, 2010)
Hydrodynamic studies of trickle bed reactors (TBRs) are essential for the design and prediction of their performance. The hydrodynamic characteristics involving pressure drop and dynamic liquid saturation are greatly affected by the physical properties of the liquids. In the present study experiments have been carried out in a concurrent downflow air - liquid trickle bed reactor to investigate the dynamic liquid saturation and pressure drop for the water (non-foaming) and 3% polyethylene glycol and 4% polyethylene glycol foaming liquids in the gas continuous regime (GCF) and foaming pulsing regime (FP). In the GCF regime the dynamic liquid saturation was found to increase with increase in liquid flow rate for non-foaming and foaming liquids. While for 3% and 4% polyethylene glycol solutions the severe foaming was observed in the high interaction regime and the regime is referred to as foaming pulsing (FP) regime. The decrease in dynamic liquid saturation followed by a sharp rise in the pressure drop was observed during transition from gas GCF to FP regime. However in the FP regime, a dip in the dynamic liquid saturation was observed. The pressure drop for foaming liquids is observed to be manifolds higher compared to non-foaming liquid in the GCF regime.  © 2010 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)